2017
DOI: 10.14336/ad.2017.0829
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Baicalin and Baicalein on Cerebral Ischemia: A Review

Abstract: Ischemic stroke, producing a high mortality and morbidity rate, is a common clinical disease. Enhancing the prevention and control of ischemic stroke is particularly important. Baicalin and its aglycon baicalein are flavonoids extracted from Scutellaria baicalensis, an important traditional Chinese herb. In recent years, a growing body of evidences has shown that baicalin and baicalein could be effective in the treatment of cerebral ischemia. Pharmacokinetic studies have shown that baicalin could penetrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 106 publications
(126 reference statements)
2
98
0
2
Order By: Relevance
“…Baicalin has been extensively used in pharmaceutical and food industries due to its outstanding bioactivities. A number of in vitro and in vivo studies have demonstrated that baicalin possesses various pharmacological properties, including anti-inflammatory, anticancer, antidiabetic, antithrombotic, cardioprotective, hepatoprotective, and neuroprotective properties [ 8 , 9 ]. In particular, baicalin exhibits a variety of beneficial effects in the central nervous system (CNS) by promoting neural differentiation and inhibiting neuronal apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin has been extensively used in pharmaceutical and food industries due to its outstanding bioactivities. A number of in vitro and in vivo studies have demonstrated that baicalin possesses various pharmacological properties, including anti-inflammatory, anticancer, antidiabetic, antithrombotic, cardioprotective, hepatoprotective, and neuroprotective properties [ 8 , 9 ]. In particular, baicalin exhibits a variety of beneficial effects in the central nervous system (CNS) by promoting neural differentiation and inhibiting neuronal apoptosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scutellaria baicalensis and its constituents have been shown to have neuroprotective, antioxidant, anti-apoptotic, antiinflammatory, and anti-excitotoxicity activity (93)(94)(95)(96). One of the active constituents found in Scutellaria baicalensis, baicalein, was found to exhibit in vitro activity against various morphologic forms of B. burgdorferi and B. garinii, including log phase spirochetes, latent round bodies, and biofilm formations (97).…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein is a common component of Carthami Flos and Radix paeoniae Rubra. As an important avonoids, it has many pharmacological activities, such as antioxidant stress, anti-in ammatory, anti-excitatory toxicity, anti-apoptosis, stimulating neurogenesis and promoting the expression of neuroprotective factors [50][51][52]. Liu et al found that baicalein had protective effect on transient middle cerebral artery occlusion model rats, and could signi cantly reduce the apoptosis of ischemic penumbra cells around the ischemic infarct of middle cerebral artery occlusion (MCAO) model rats [53].…”
Section: Discussionmentioning
confidence: 99%